Tails through time: leopard population dynamics in the Little Karoo - Steyn, Lawrence (Department of Biological Sciences, 2025)
Large carnivores play a vital role in structuring our ecosystems, yet they face mounting threats such as habitat loss, prey reduction and persecution. These threats reduce their global distribution and impacts their population numbers. Protected areas can offer refuge for large carnivores, however leopards (Panthera pardus), can persist outside of these areas and often occupy mixed-use landscapes. Our understanding of how leopards persist over time in mixed-use landscapes is limited, especially in the semi-arid regions of southern Africa. This study, to the best of my knowledge, is the only multi-session maximum likelihood spatial capture-recapture (SCR) analysis to have been conducted in a semi-arid environment outside of a protected area in Southern Africa. The study aimed to estimate leopard population changes over time and to investigate the possible drivers affecting density, using three surveys (2012, 2017, 2022), in the mixed-use landscape of the Little Karoo in the Western Cape, South Africa. In 2012, a total of 141 paired camera stations were used for a total of 13,050 trap days resulting in 29 unique leopard captures. In 2017, a total of 40 paired camera stations were used for a total of 2,128 trap days resulting in 18 unique leopard captures and in 2022 a total of 64 paired camera stations were used for a total of 8,997 trap days resulting in 37 unique leopard captures. The best performing density model indicated an increasing population trend over the study period which included a trend term on density (D~year) and an interaction term (individual session*sex) on λ0 (capture rate) and σ (spatial decay). Density estimates (Standard Error) for leopard populations for the three surveys 2012, 2017, and 2022, were 0.52 (± 0.11), 0.70 (± 0.08), and 0.95 (± 0.08) leopards per 100 km2, respectively. Terrain ruggedness, elevation, vegetation type and distance from major rivers were all important drivers in leopard density in the Little Karoo. Indicating that high lying areas provide suitable refuge for leopards and are key areas for movement corridor planning. These density estimates are similar to previous single maximum likelihood SCR density estimate studies in the Little Karoo and the Western Cape province. Results from this study indicate the leopards have persisted in the Little Karoo over the study period and suggest that the population may be increasing. Further research on what is driving this population shift is needed, but the results serve as an encouraging sign for leopard conservation in the Little Karoo